Volume 1B: Combustion, Fuels and Emissions 2013
DOI: 10.1115/gt2013-95904
|View full text |Cite
|
Sign up to set email alerts
|

A Skeletal Mechanism for the Reactive Flow Simulation of Methane Combustion

Abstract: A skeletal mechanism for the prediction of NOx emissions from methane combustion at gas turbine conditions is developed in the present work. The goal is a mechanism that can be used in computational fluid dynamic modeling of lean premixed (LPM) combustors. A database of solutions from 0-D, adiabatic, homogeneous reactors (PSRs) is computed using CHEMKINPRO [1] over a parameter space chosen to include pressures from 1 to 30 atm, equivalence ratios from 0.4 to 1.0, and mean PSR residence times from slightly grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…In the first LES, the turbulent chemistry model is eddy dissipation concept EDC. Reaction mechanism used to model the chemical reaction is a "skeletal mechanism" including 22 species of the methane combustion based on GRI 3.0 [12].…”
Section: Large Eddy Simulation (Les)mentioning
confidence: 99%
“…In the first LES, the turbulent chemistry model is eddy dissipation concept EDC. Reaction mechanism used to model the chemical reaction is a "skeletal mechanism" including 22 species of the methane combustion based on GRI 3.0 [12].…”
Section: Large Eddy Simulation (Les)mentioning
confidence: 99%
“…The mixing rate limit is specifically important in the design of a practical SCWG system. The application of limiting rate models to the laboratory and industrial reacting systems can be found in [73, 74, 75].…”
Section: Main Textmentioning
confidence: 99%
“…[59][60][61][62] model is often used in modeling industrial combustors due to its low computational cost. 64 To incorporate combustion chemistry in flow simulations, Magnussen et al proposed an eddy dissipation concept (EDC) model, [65][66][67] which was used to model turbulent combustion, including laboratory reactors 68,69 and industrial burners. Modeling of laboratory system with reduced and skeletal chemical kinetics mechanism have shown promising results and identified a shift in flame location, quenching in chain branching reactions and presence of high concentrations of OH radicals approaching LBO.…”
Section: Introductionmentioning
confidence: 99%